Mortality among very low birth weight infants after hospital discharge in a low resource setting - Yaser Abdallah; Flavia Namiiro; Jolly Nankunda; Jamiru Mugalu; Yvonne Vaucher (BMC, 2018)
Abstract Background Early discharge of very low birth weight infant (VLBW) in low resource settings is inevitable but to minimize mortality of these infants after discharge we need to identify the death attributes. Method A prospective cohort was conducted among 190 VLBW infants discharged from Mulago Special Care Baby Unit (SCBU) with discharge weight of < 1500 g over an 8 months period. These infants were followed up with the aims of determining the proportion dead 3 months after discharge, identifying factors associated and possible causes of death. Relevant data were captured, transferred in to STATA and imported to SPSS 12.0.1 for analysis. To determine factors associated with mortality bi-variable and multivariable regressions were conducted. A p-value of < 0.05 was considered significant and 95% confidence interval was used. Results Of the enrolled infants 164 (86.3%) completed follow up. The median gestational age of study participants was 32 weeks (range 26-35 weeks), the mean discharge weight was 1119 g (range 760-1470 g), and 59.8% were small for gestational age (SGA). During follow up 32 (19.5%) infants died. Infants discharged with weight of < 1200 g accounted for 81.2% of the deaths. Majority of the deaths (68.7%) occurred in the first month after discharge. Factors independently associated with mortality were discharge weight < 1000 g (OR 3.10, p 0.015) and not being SGA (OR 3.54, p 0.019). The main causes of death were presumed sepsis 50.0% and suspected cot death (25.0%). Conclusion Mortality after hospital discharge among VLBW infants is high. Discharge at weight < 1200 g may not be a safe practice. Measures to prevent sepsis and suspected cot death should be addressed prior to considering early discharge of these infants.